2003
DOI: 10.1242/jeb.00485
|View full text |Cite
|
Sign up to set email alerts
|

Acutely elevated vasopressin increases circulating concentrations of cortisol and aldosterone in fasting northern elephant seal (Mirounga angustirostris) pups

Abstract: SUMMARYThe physiological actions of vasopressin (VP) in marine mammals are not well defined. To help elucidate its hormonal and renal effects in this group of mammals, northern elephant seal (Mirounga angustirostris) pups(N=7; 99±4 kg) were first infused with 0.9% saline (control;220 ml), followed 24 h later with VP (as a 20 ng kg-1 bolus, then 2 ng kg-1 min-1 for approximately 35 min in 225±16 ml saline). During both control and VP periods, blood samples were collected prior to infusion, and 15, 30, 60, 120 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Mean aldosterone concentrations from nursing and postnursing adult female harp seals (300 pg/mL) were similar to those reported here during the late period ( pg/mL) and for lactating adult 254 ‫ע‬ 39 female northern elephant seals (380 pg/mL; D. E. Crocker, unpublished data). In elephant seal pups, mean aldosterone concentrations increased from 200 to 1,500 pg/mL during the first 7 wk of the postweaning fast (Ortiz et al 2000(Ortiz et al , 2002a(Ortiz et al , 2002b(Ortiz et al , 2003Houser et al 2001), representing a 7.5-fold increase, whereas the increase in fasting adult males over a comparable duration was only 1.7-fold. An age-related change in the sensitivity of aldosterone response to fasting may be but one potential explanation for the discrepancy in the degree of change of aldosterone between pups and adults.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Mean aldosterone concentrations from nursing and postnursing adult female harp seals (300 pg/mL) were similar to those reported here during the late period ( pg/mL) and for lactating adult 254 ‫ע‬ 39 female northern elephant seals (380 pg/mL; D. E. Crocker, unpublished data). In elephant seal pups, mean aldosterone concentrations increased from 200 to 1,500 pg/mL during the first 7 wk of the postweaning fast (Ortiz et al 2000(Ortiz et al , 2002a(Ortiz et al , 2002b(Ortiz et al , 2003Houser et al 2001), representing a 7.5-fold increase, whereas the increase in fasting adult males over a comparable duration was only 1.7-fold. An age-related change in the sensitivity of aldosterone response to fasting may be but one potential explanation for the discrepancy in the degree of change of aldosterone between pups and adults.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously shown that an acute intravenous infusion of AVP induced a rapid (within 15 min) increase in circulating cortisol in fasting pups, suggesting that AVP stimulated a neuroendocrine response in fasting seals (Ortiz et al 2003). In the current study, cortisol was measured simultaneously (data not reported here) to address the potential concern that the observed concentrations of AVP were the product of a neuroendocrine response induced by the sampling protocol and did not necessarily reflect an osmotic response.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations